Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Nagel, Christof; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Funnel control of linear systems under output measurement losses - Lanza, Lukas Johannes; Berger, Thomas

Network and Service Coordination: Conventional and Machine Learning Approaches" - Schneider, Stefan Balthasar

A Reference Process Model for Usage Data-Driven Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 55th Hawaii International Conference on System Sciences)
Cyber-physical systems generate and collect huge amounts of usage data during operation. Analyzing these data may enable manufacturing companies to identify weaknesses and learn about the users of their products. Such insights are valuable in the early phases of product development like product planning, as they facilitate decision-making for product improvement. The analysis and exploitation of usage data in product planning, however, is a new task for manufacturing companies. To reduce mistakes and improve the results, companies should build upon a suitable reference process model. Unfortunately, established models for analyzing data cannot be easily applied for product planning. In this paper, we propose a reference process model for usage data-driven product planning. It builds on three well-established models for analyzing data and addresses the unique characteristics of usage data-driven product planning. Finally, we customize the model for a manufacturing company and demonstrate how it could be implemented in practice.

Enhancing Human-in-the-Loop Adaptive Systems through Digital Twins and VR Interfaces - Yigitbas, Enes; Karakaya, Kadiray; Jovanovikj, Ivan; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Collaborative Software Modeling in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Search Space Characterization for Approximate Logic Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Reuter, Lucas David; Platzner, Marco (2022 59th ACM/IEEE Design Automation Conference (DAC))

MUSCAT: MUS-based Circuit Approximation Technique - Witschen, Linus Matthias; Wiersema, Tobias; Artmann, Matthias; Platzner, Marco (Design, Automation and Test in Europe (DATE))

Exact output tracking in prescribed finite time via funnel control - Lanza, Lukas Johannes
We extend a recent result in high-gain feedback output tracking control to achieve exact tracking within finite time, i.e., the output of a system and its relevant derivatives have certain exact values at a predefined finite time. We propose a new funnel control scheme achieving this, whereas the error between the reference and the output evolves within prescribed bounds. Applications of this are, for instance, linking up two parts of a train, or docking spaceships.

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse des Versagensverhaltens geklebter Stahl-Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

High-Bandwidth Arbitrary Signal Detection Using Low-Speed Electronics - Meier, Janosch; Singh, Karanveer; Misra, Arijit; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (IEEE Photonics Journal)
The growing demand for bandwidth and energy efficiency requires new solutions for signal detection and processing. We demonstrate a concept for high-bandwidth signal detection with low-speed photodetectors and electronics. The method is based on the parallel optical sampling of a high-bandwidth signal with sinc-pulse sequences provided by a Mach-Zehnder modulator. For the electronic detection and processing this parallel sampling enables to divide the high-bandwidth optical signal with the bandwidth B into N electrical signals with the baseband bandwidth of B/(2N) . In proof-of-concept experiments with N=3 , we present the detection of 24 GHz optical signals by detectors with a bandwidth of only 4 GHz. For ideal components, the sampling and bandwidth down-conversion does not add an excess error to the signals and even for the non-ideal components of our proof-of-concept setup, it is below 1%. Thus, the rms error for the measurement of the 24 GHz signal was reduced by a factor of about 3.4 and the effective number of bits were increased by 1.8.

Methodenentwicklung für die Simulation mechanischer Fügeprozesse mit besonderer Berücksichtigung fügespezifischer Reibverhältnisse - Rossel, Moritz Sebastian; Meschut, Gerson

Evaluation of Algorithms for the Node Capacitated Clique - Roopa, Rajanna

A Versatile Metasurface Enabling Superwettability for Self‐Cleaning and Dynamic Color Response - Lu, Jinlong; Sain, Basudeb; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Zentgraf, Thomas (Advanced Optical Materials)
Metasurfaces provide applications for a variety of flat elements and devices due to the ability to modulate light with subwavelength structures. The working principle meanwhile gives rise to the crucial problem and challenge to protect the metasurface from dust or clean the unavoidable contaminants during daily usage. Here, taking advantage of the intelligent bioinspired surfaces which exhibit self-cleaning properties, a versatile dielectric metasurface benefiting from the obtained superhydrophilic or quasi-superhydrophobic states is shown. The design is realized by embedding the metasurface inside a large area of wettability supporting structures, which is highly efficient in fabrication, and achieves both optical and wettability functionality at the same time. The superhydrophilic state enables an enhanced optical response with water, while the quasi-superhydrophobic state imparts the fragile antennas an ability to self-clean dust contamination. Furthermore, the metasurface can be easily switched and repeated between these two wettability or functional states by appropriate treatments in a repeatable way, without degrading the optical performance. The proposed design strategy will bring new opportunities to smart metasurfaces with improved optical performance, versatility, and physical stability.

Aufarbeitung und lmplementierung von DAG-Rider - Korzeczek, Sebastian

Hybrid Routing in Three Dimensions - Nachtigall, Marcel

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Striewe, Marius; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Steinmann, Paul (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Reproducibility in Polymer Laser Sintering - Klippstein, Sven Helge